(untitled) (Bangladesh Journal of Medical Physics, 2018)
Spirometry, or measurement of respiration conventionally involves measurement of the time variation of volume or flow of air breathed in or out through the mouth using an air-flow sensor. Electrical impedance of thorax changes during breathing and conceptually this modality should be applicable in spirometry, but no attempts have been made so far. This paper describes the development of an electrical impedance based spirometer placing electrodes on four limbs so that the whole lung volume may contribute to the measurement. An impedance based measurement system (IBS) consisting of a constant current drive at 11 kHz and necessary voltage measurement circuitry was designed and developed for this purpose. A portable oscilloscope (PicoScope 2208A) was used for acquisition of the measured voltage signal to a PC and an algorithm in Matlab software was used to demodulate the time varying impedance from a carrier signal. The variation of impedance with time during forced expiration as measured by the implemented impedance measurement system was compared with that obtained using a standard bellows type commercial spirometer (Vitalograph) on eight volunteers, between 22 and 32 years of age. The subjects included smokers, non-smokers, and asthma patients. Repeatability of the measurements were satisfactory. The correlation coefficient between the spirogram obtained using the IBS and that obtained using standard spirometer varied from 0.81 to 0.99 indicating preliminary success of the proposed technique. However, a possible source of error is the bending of the body during forced expiration which, if prevented, may give a better outcome. Bangladesh Journal of Medical Physics Vol.9 No.1 2016 17-27